RNA vaccines: The dawn of a new age for tuberculosis? - Junli Li; Dong Liu; Xiaochi Li; Jiazheng Wei; Weixin Du; Aihua Zhao; Miao Xu (Human Vaccines & Immunotherapeutics)
Since 2019, there has been a growing focus on mRNA vaccines for infectious disease prevention, particularly following the emergence of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). mRNA vaccines offer advantages such as rapid production and the ability to induce robust cellular and antibody responses, which are essential for combating infections that require cell-mediated immunity, including Tuberculosis (TB). This review explores recent progress in TB mRNA vaccines and addresses several key areas: (1) the urgent need for new TB vaccines; (2) current advancements in TB vaccine development, and the advantages and challenges of mRNA technology; (3) the design and characteristics of TB mRNA vaccines; (4) the immunological mechanisms of TB mRNA vaccines; (5) manufacturing processes for TB mRNA vaccines; and (6) safety and regulatory considerations. This interdisciplinary review aims to provide insights for researchers working to address critical questions in TB mRNA vaccine development.